A study on solar assisted domestic refrigeration system [microfilm] - AbdelAzim Mohamed Ali (Skudai : Universiti Teknologi Malaysia, 1999)
Thesis (PhD) - Fakulti Sains, Universiti Teknologi Malaysia, 1999